Performance analysis in Olympic triathlon - Pupisova, Z.; Pavlik, J. (Slovak Journal of Sport Science, 2018)
The objective of this study is to determine the dependence between the overall performance in triathlon and the individual events within it in the observed period of 2015-2018. The presented study deals especially with Olympic triathlon under the auspices of the International Triathlon Union. It includes 41 races with the overall number of analysed results being n=1213. The results show that the running part has the average value of r=0.85 (p<0.01) based on the correlation coefficient, which means a very high dependence in the results. The other two sport events have not showed such a high dependence.